2011
DOI: 10.1097/psy.0b013e31821a196f
|View full text |Cite
|
Sign up to set email alerts
|

Leptin as a Neuroactive Agent

Abstract: Clinical research suggests an important role of leptin in psychiatric illnesses. Given the morbidity associated with mental illness, clinical research on the role of leptin and related novel therapeutic modalities is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…Nevertheless, the result of an interactive effect of leptin and waist circumference in predicting depressive symptoms is consistent with the hypothesis that it is not the absolute concentration of leptin that is correlated with mood but rather its ability to induce an effect at the receptor/post-receptor level(Lu, 2007; Zupancic and Mahajan, 2011). In this context, reduced leptin signaling to central nervous systems may be due to both leptin insufficiency in lean subjects or functional resistance-related hyperleptinemia in obese persons.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Nevertheless, the result of an interactive effect of leptin and waist circumference in predicting depressive symptoms is consistent with the hypothesis that it is not the absolute concentration of leptin that is correlated with mood but rather its ability to induce an effect at the receptor/post-receptor level(Lu, 2007; Zupancic and Mahajan, 2011). In this context, reduced leptin signaling to central nervous systems may be due to both leptin insufficiency in lean subjects or functional resistance-related hyperleptinemia in obese persons.…”
Section: Discussionsupporting
confidence: 82%
“…From a clinical point of view, these data sustain the idea that the key to understand the pathophysiology of leptin may lie in its function and its impaired central action and not merely in its circulating level. Therefore, in obese depressed patients therapeutic interventions on leptin downstream pathways should target leptin central resistance rather than leptin itself(Lu, 2007; Zupancic and Mahajan, 2011). A recent study(Yamada et al, 2011) showed that leptin homeostatic and antidepressant effect were impaired in the hippocampus of diet-induced obese mice, resulting in a severe depressive state despite hyperleptinemia; diet substitution and weight loss in the obese mice normalized leptin levels and restored the antidepressant effect of leptin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given evidence that obesity is associated with neurocognitive deficits, such that higher BMIs are associated with greater deficits, the improvement in neurocognitive functioning following bariatric surgery may be due, at least in part, to weight loss associated with the surgical intervention. However, given the effects of bariatric surgery on a number of systems and functions that have been linked with cognitive functioning (e.g., insulin resistance, leptin levels; Ballantyne et al, 2006; Beckman et al, 2010; Park, 2001; Zupancic & Mahajan, 2011), the specific mechanisms underlying these changes remains unclear.…”
Section: Introductionmentioning
confidence: 99%